Centromeres as universal hotspots of DNA breakage, driving RAD51-mediated recombination during quiescence - Saayman, X; Graham, E; Nathan, WJ; Nussenzweig, A; Esashi, F (Cell Press, 2023)
Centromeres are essential for chromosome segregation in most animals and plants yet are among the most rapidly evolving genome elements. The mechanisms underlying this paradoxical phenomenon remain enigmatic. Here, we report that human centromeres innately harbor a striking enrichment of DNA breaks within functionally active centromere regions. Establishing a single-cell imaging strategy that enables comparative assessment of DNA breaks at repetitive regions, we show that centromeric DNA breaks are induced not only during active cellular proliferation but also de novo during quiescence. Markedly, centromere DNA breaks in quiescent cells are resolved enzymatically by the evolutionarily conserved RAD51 recombinase, which in turn safeguards the specification of functional centromeres. This study highlights the innate fragility of centromeres, which may have been co-opted over time to reinforce centromere specification while driving rapid evolution. The findings also provide insights into how fragile centromeres are likely to contribute to human disease.